The question of plurality and universal affirmation: A dialogue of thought between Arendt and Badiou - Akin, Zanan (HannahArendt.net, 2024)
The word protest originates in pro-testari and means “to testify or attest”. So, this word should actually entail an affirmative moment of “demonstration of being for something”. It is a remarkable detail, though, that with the establishment of streets protest as a common and legitimate way of expressing political opposition in modernity, the meaning of pro-testari seems to have been inversed to con-testari, which means to dispute or oppose. So, protest has been gaining a predominant negative moment of “demonstration of being against something.” Alain Badiou notes this inversion. In that manner he has been talking in recent years increasingly of an inability of affirmation in in the street protest movements. According to Badiou, this inability first became clearly visible with the occupy movements and has reached a much more dangerous shape with the Yellow Vests protests, such that it led Badiou to coin a new term, which is “weak negation.” The point in this coining is that a weak negation remains separated from any universal affirmation and worse: As it cannot affirm anything which transcends the inner constitution of what it negates, it ends up vouching for the existing order of things, which it supposedly negates, as the only possible one.1 During the COVID protests, Badiou’s diagnosis has shifted to an overall disorientation. His recently published booklet, Remarks on the disorientation of the world entails in that regard a striking aspect which provokes a very fruitful dialogue of thought with Hannah Arendt. Regarding the fact that these protests had such “diverse” participants ranging from self-declared “democrats”, “authentic nationalists”, “classical liberals” to “esoteric ecologists” and a branch of the “far left”, Badiou claims that what brought this hitherto unimaginable ensemble together has actually been nothing but a “cultus of me” which expressed itself in a shared obsession with “individual liberties.” In terms of the logic of what we could call a political action with Arendt, which has its only basis in the “plurality of men inhabiting the world”2, does not the cultus of me bring with itself a quite remarkable paradox here? For regarding the heterogeneity of the groups which allegedly came together in the COVID protests, what we can detect is the strange fact that everyone’s own me as the most individual and singular, thus the least “common”, has become the sole ground of the “plural.” If we frame the ultimate goal of those gatherings in that regard as refusing and preventing any collective action which takes into account that others who are not me also exist, then we must arrive at a paradox conclusion which is that a group of people may come together to prevent any consideration of “living in the world together”3. This striking paradox invites us to think on the question of “plurality” in street protests and its link to the question of negation and affirmation in an “action”: So, what is actually the basis of plurality in a street protest? Is being a mere indifferent equivalency of the infinitely diverse more-than-one sufficient to call a gathering “plural”? Is not a moment necessary in a gathering, which can hold this more-than- one together? The crux of this issue is exactly here: How to determine this moment, which allows us to call a group “plural” in the sense Arendt would understand the term, rather than a mere indifferent more-than-one? Can “a will to negate” be a sufficient basis to found a plurality, as far as we keep the criterion of plurality of action as the appearance of a worldly reality which comes into expression when Arendt says that “only where things can be seen by many in a variety of aspects without changing their identity, so that those who are gathered around them know they see sameness in utter diversity, can worldly reality truly and reliably appear”4? So, is a collective negation sufficient for a worldly reality to appear? Or does a gathering in order to be called plural, capable of action and letting a worldly reality reappear, require a universal point of affirmation, which can only realize the “sameness in utter difference?” Overall: Is the only point that a protest today “attests” the number of people who can gather around something that they all are against? How can we then comprehend a conception of “plurality” if it recognizes the interest in one’s me and its individual liberty as the sole possible basis of inter-esse? 1 Alain Badiou: Remarques sur la désorientation du monde, 2022 Paris, P. 22 2 Hannah Arendt: The Human Condition, 1959 Chicago-London P. 7 3 Hannah Arendt: The Human Condition, P. 53